Degradation of Polychlorinated Biphenyls (PCBs) in Water Matrix Using UV/H202 Efect Of Initial PCB Concentration and Analysis of Reaction - Centeno, Carmela R; Estrellan, Carl Renan E; Maridable, Julius B; Abella, Leonila C; Gallardo, Susan M (ASEAN Journal of Chemical Engineering, 2006)
his study investigated the effect of the different initialconcentrations of polychlorinated biphenyls (PCBs) on its degradation in water matrix using UVIHP2 and on the formation of reaction intermediates or products. Simulated PCB-contaminated water solution was subjected to irradiation with 17 W, 254 nm wavelength UV lamp in a batch tubular reactor. The ratio of oxidant to PCBs, in terms of Arodor 1260, was based on 2,800 I!L HP2 isto 40 ppm PCB. Samples were extracted from the matrix by solid-phase extraction (SPE) method using C18 cartridges with hexane and ethyl acetate as solvents. The samples were analyzed using Gas Chromatography-Electron Capture Detector System (GC-ECD) to determine the concentration of PCBs in the samples and pH was monitored every sampling time. The analysis of chloride (CI-)ion concentration in the samples was done using Argentometric titration. Determination of reaction intermediates and products was carried out with 40 ppm PCB concentration using Gas Chromatography-Mass Spectroscopy (GC-MS) system. A decrease in pH in the early stages of degradation was observed and the higher the initial concentration of PCB the greater was the drop in pH. The PCB degradation profile showed that from 1 to 40 ppm initial concentration, the degradation efficiency of UVIHP2 increased with increasing initial PCB concentration. At 80 ppm, however, it was observed that there was a decrease in the efficiency of the system. The inorganic chloride ions produced indicate that dechlorination took place in the system. GC-MS analysis verified the decrease in concentration of PCBs in the solution and showed the preferential attack of the UV/HP2 to PCBs over long chain saturated alkanes or waxes which contained the PCBs.